Global Issues in Budgeting and Financing Systems (RM, BLU, and UKT) for World-Class Education: A Case Study at UIN SUKA Yogyakarta - Wardatul Jannah; Kaspul Anwar Us; Fridiyanto (Future Techno-Science, 2025)
Higher education institutions today are not only centers of knowledge development but also expected to meet international standards as World Class Universities (WCU). One major challenge in achieving this status lies in the effective, transparent, and output-oriented management of budgeting and financing systems. UIN Sunan Kalijaga Yogyakarta, in its effort to become a World Class Education (WCE) institution, faces significant global pressures such as declining state budget allocations, international accreditation demands, increasing PhD faculty ratios, and the need for campus expansion. This study aims to examine how budgeting and financing systems—Rupiah Murni (RM), Public Service Agency (BLU), and Single Tuition Fee (UKT)—are implemented, the global issues influencing higher education financing, and how these systems support institutional transformation. Using a qualitative descriptive approach and case study method, the research reveals that UIN Sunan Kalijaga adopts a hybrid financing model combining state funds, institutional revenues, and student contributions. The BLU system grants financial flexibility through service income and asset optimization, while UKT is managed transparently to ensure affordability. However, global issues such as funding cuts, education inflation, and dependency on government-issued Islamic bonds (SBSN) pose ongoing challenges. In this context, financial systems become critical drivers for improving infrastructure, academic quality, and global engagement. Initiatives like endowment fund development signal a strategic shift toward long-term financial sustainability. Ultimately, budgeting and financing serve not only administrative functions but also act as key catalysts in achieving WCU standards.